Quatro Casas numa Vinha - António Sampaio Ferreira Coelho (2019)
This work, that arises from a familial request, consists in designing four houses at Quinta de Tourais, in the center of the Douro Region, with the purpose of widening the range of products and services of the estate. Knowing the circumstances in which our proposal emerges, a strategy for the property as whole became necessary. Our proposal relies on a oriented research, in which the Douro and architecture without architects, are the main themes that help us define and solve the problem we set ourselves to. We intend to explore the permeability of architecture as a discipline dependant of many factors of political, economical and social order. In this context, and with the will of improving our critical spirit, we reflect about the role that the architects should play in our societies. The emphazis is put on the responsability, and we hope that this exercise can become an example and spread awareness about the importance of thoughtful planning.